Decreased expression of thymus‐specific proteasome subunit β5t in Down syndrome patients. Issue 2 (13th February 2015) - Tomaru, Utano; Tsuji, Takahiro; Kiuchi, Shizuka; Ishizu, Akihiro; Suzuki, Akira; Otsuka, Noriyuki; Ito, Tomoki; Ikeda, Hitoshi; Fukasawa, Yuichiro; Kasahara, Masanori
<x xml:space="preserve">Abstract</x> Aims The majority of patients with Down syndrome (DS), trisomy 21, have morphologically abnormal thymuses and present with intrinsic immunological abnormalities affecting mainly the cellular immune response. The aim of this study was to examine whether the expression of functionally important molecules is altered in thymic stromal cells in patients with DS. Methods and results We analysed thymic tissues from patients with trisomy 13 (n = 4), trisomy 18 (n = 14) and trisomy 21 (n = 13) for histological alterations, and for the expression of functionally important molecules such as β5t, a thymoproteasome subunit, and cathepsins L and S. In patients with trisomy 13 and trisomy 18, the thymus was morphologically normal or showed only mild depletion of cortical thymocytes. In contrast, the thymus showed variable histological changes in patients with trisomy 21; six of 13 cases showed severe depletion of thymocytes accompanied by the disappearance of thymic lobular architecture. In such thymuses, spindle‐shaped keratin‐positive cells were densely distributed, and expression of β5t, but not of cathepsin L, was markedly decreased. Conclusions The present study suggests that abnormal thymic architecture and decreased expression of functionally important molecules in thymic stromal cells may be involved in immunological abnormalities in DS patients.